Putative Neuroprotective and Neurotoxic Kynurenine Pathway Metabolites Are Associated with Hippocampal and Amygdalar Volumes in Subjects with Major Depressive Disorder - Savitz, Jonathan; Drevets, Wayne C; Smith, Chelsey M; Victor, Teresa A; Wurfel, Brent E; Bellgowan, Patrick SF; Bodurka, Jerzy; Teague, T Kent; Dantzer, Robert (Neuropsychopharmacology (New York, N.Y.), 2015)
Inflammation-related changes in the concentrations of kynurenine pathway metabolites occur in depression secondary to medical conditions but are not firmly established in primary mood disorders. Reductions in hippocampal and amygdalar volume that putatively reflect dendritic atrophy are widely reported in major depressive disorder (MDD). Here we tested whether the relative serum concentrations of putatively neuroprotective (kynurenic acid (KA)) and neurotoxic (3-hydroxykynurenine (3HK) and quinolinic acid (QA)) kynurenine pathway metabolites were altered in primary MDD and whether these metabolites were associated with hippocampal and amygdalar volume. A total of 29 moderately to severely depressed unmedicated subjects who met DSM-IV criteria for MDD and 20 healthy controls (HCs) completed a structural MRI scan and provided blood sample for kynurenine metabolite analysis, performed using high-performance liquid chromatography with tandem mass spectrometry. Cytokine concentrations were measured with ELISA and gray matter volumes were measured with the automated segmentation software, FreeSurfer. An a priori defined variable of interest, the KA/QA ratio, a putative neuroprotective index, trended lower in the MDD versus the HC group and correlated negatively with anhedonia but positively with the total hippocampal and amygdala volume in the MDD subjects. The post hoc data reduction methods yielded three principal components. Component 1 (interleukin-1 receptor antagonist, QA, and kynurenine) was significantly elevated in MDD participants versus the HCs, whereas component 2 (KA, tryptophan, and kynurenine) was positively correlated with hippocampal and amygdala volume within the MDD group. Our results raise the possibility that an immune-related imbalance in the relative metabolism of KA and QA predisposes to depression-associated dendritic atrophy and anhedonia.